2001
DOI: 10.1023/a:1011909107858
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: A study was conducted to determine the location and distribution of PAH and PAH-degrading bacteria in different aggregate size fractions of an industrially polluted soil. The estimation of PAH-degrading bacteria using an MPN microplate technique indicated that these bacteria are most numerous in the aggregate size fractions corresponding to fine silt (2-20 microm) and clay (<2 microm) compared to larger fractions or unfractionated soil. PAH concentrations were also highest in the aggregate size fraction corres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(13 citation statements)
references
References 41 publications
0
13
0
Order By: Relevance
“…Recent literature on the methods of removal of phenol and their compounds from wastewater focuses on adsorption and microbial biodegradation process [61][62][63][64]. Certain species like Pseudomonas sp.…”
Section: Biomassmentioning
confidence: 99%
“…Recent literature on the methods of removal of phenol and their compounds from wastewater focuses on adsorption and microbial biodegradation process [61][62][63][64]. Certain species like Pseudomonas sp.…”
Section: Biomassmentioning
confidence: 99%
“…Furthermore, Vogel et al [25] reported previously that QM and QMC soils incubated over a long-term period contained more aggregates than soils with illite. It is known that the biodegradation of PAHs is restricted in aggregates [2], [47], [48], [49]. Montmorillonite is an expandable clay mineral with a high specific surface area which makes possible that phenanthrene was separated from bacterial cells by surface sorption or entrapment in small pores [10], [50].…”
Section: Discussionmentioning
confidence: 99%
“…Different parameters can severely affect the efficiency of the methods, as for instance the exposure time of the contaminant in soil [1], soil structure [2], pH [3], temperature [3], sorptive interfaces [4], and the organic carbon content [5]. In addition, the accessibility to oxygen may be of importance, since the fastest and most often used microbial pathway of PAH degradation involves the oxidation of the ring-structure via dioxygenases [6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recognizing sediment as an assembly of different sizes of particles, a handful of researchers investigated the availability of PAHs also at the particle size scale. For instance, in suspensions, bacteria density was found to be lower on sand particles than on silt or clay particles, leading to a lower biodegradation rate of PAHs on sand (Amellal et al 2001; Xia and Wang 2008). Talley et al (2002), by separating a dredged sediment into coal-derived fraction and clay/silt fraction, showed that desorption and bioavailability of PAHs were more related to properties such as BC content of specific size fractions, rather than the size scale itself.…”
Section: Introductionmentioning
confidence: 99%